2022
DOI: 10.1177/1866802x221127712
|View full text |Cite
|
Sign up to set email alerts
|

Is it Worth the Risk? Grievances and Street Protest Participation During the COVID-19 Pandemic in Chile

Abstract: The COVID-19 pandemic started in Chile as the country was experiencing massive protests and a deep political crisis. Sanitary measures restricting movement and gatherings were implemented while the process of constitutional change responding to this crisis developed. In this context of conflict, we study why people continued participating in street protests despite the restrictions and the health risks involved. Using two surveys, we test key factors addressed in extant scholarship: biographical availability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(68 reference statements)
0
5
0
1
Order By: Relevance
“…Las manifestaciones masivas se mantuvieron con regularidad hasta marzo de 2020, momento en que cesaron para contener la crisis sanitaria causada por la pandemia de COVID-19 (Donoso et al, 2022). En este contexto, el Gobierno impuso medidas de restricción a las libertades individuales, mediante la declaración de estado de catástrofe en marzo del mismo año.…”
Section: Violencia En El Estallido Social En Chileunclassified
“…Las manifestaciones masivas se mantuvieron con regularidad hasta marzo de 2020, momento en que cesaron para contener la crisis sanitaria causada por la pandemia de COVID-19 (Donoso et al, 2022). En este contexto, el Gobierno impuso medidas de restricción a las libertades individuales, mediante la declaración de estado de catástrofe en marzo del mismo año.…”
Section: Violencia En El Estallido Social En Chileunclassified
“…Emigration can also signal grievances that could trigger feelings of relative deprivation (Folger, 1986;Galais and Lorenzini, 2017). As recent research has found, grievances are one of the most influential factors of street protest participation, especially in anomalous periods such as the pandemic, where perceived health risks did not diminish the propensity of protest participation (Donoso et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rooted in longstanding grievances about socioeconomic inequalities, elite corruption, and political detachment (Somma et al 2020;González and Le Foulon 2020), this social uprisingpopularly known as estallido social-threatened the country's stability and forced political elites to agree on a constitutional referendum as a way out the crisis. While demonstrations temporarily eased with the pandemic outbreak in March 2020, they returned to the streets once public health circumstances improved, performing less massive yet more disruptively (Donoso et al 2022). This raised increasing concern among citizens who witnessed severe deterioration of public spaces.…”
Section: Rising Security Concerns: Violent Protests Criminal Violence...mentioning
confidence: 99%